Unveiling the genetic architecture for lodging resistance in rice (Oryza sativa. L) by genome-wide association analyses - Rashid, Muhammad Abdul Rehman; Zhao, Yong; Azeem, Farrukh; Zhao, Yan; Ahmed, Hafiz Ghulam Muhu-Din; Atif, Rana Muhammad; Pan, Yinghua; Zhu, Xiaoyang; Liang, Yuntao; Zhang, Hongliang; Li, Danting; Zhang, Zhanying; et al. (Frontiers in Genetics, 2022)
Lodging is one of the major abiotic stresses, affecting the total crop yield and quality. The improved lodging resistance and its component traits potentially reduce the yield losses. The section modulus (SM), bending moment at breaking (M), pushing resistance (PR), and coefficient of lodging resistance (cLr) are the key elements to estimate the lodging resistance. Understanding the genetic architecture of lodging resistance-related traits will help to improve the culm strength and overall yield potential. In this study, a natural population of 795 globally diverse genotypes further divided into two (indica and japonica) subpopulations was used to evaluate the lodging resistance and culm strength-related traits. Significant diversity was observed among the studied traits. We carried out the genome-wide association evaluation of four lodging resistance traits with 3.3 million deep resolution single nucleotide polymorphic (SNP) markers. The general linear model (GLM) and compressed mix linear model (MLM) was used for the whole population and two subpopulations, while a 1000-time permutation test was performed to remove the false positives. A total of 375 nonredundant QTLs were observed for four culm strength traits on 12 chromosomes of the rice genome. Then, 33 pleiotropic loci governing more than one trait were mined. A total of 4031 annotated genes were detected within the candidate genomic region of 33 pleiotropic loci. The functional annotations and metabolic pathway enrichment analysis showed cellular localization and transmembrane transport as the top gene ontological terms. The in-silico and in-vitro expression analyses were conducted to validate the candidate three candidate genes in a pleiotropic QTL on chromosome 7. It validated the OsFBA2 as a candidate gene to contribute to the lodging resistance in rice. The haplotype analysis for the candidate gene revealed a significant functional variation in the promoter region of the candidate gene. Validation and introgression of alleles that are beneficial to induce culm strength may be employed in rice breeding for lodging resistance.